(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article is based on data from farms specializing in horticulture. Factors affecting horticultural productivity relate to linear, mixed (combined), logarithmic and semi-logarithmic econometric models, optimally isolated and analyzed among the found models.